iPad jako narzędzie edukacyjnej zmiany? Porównawcze badanie wdrożenia projektu edukacyjnego w Libii i Polsce - Kopciewicz , Lucyna; Bougsiaa, Hussein (Studia Edukacyjne, 2019)
This comparative small-scale (Libyan and Polish sample) qualitative study investigates two educational models of iPads’ implementation and integration with the overall pedagogical objectives in early education in Libya and Poland. The basic methodological frame was video-ethnography supplemented by semi-structured interviews with parents, teachers and children. The questions asked were designed to recognize how technology might fit within the school’s overall vision. The results indicate that each technology initiative can be potentially transformative for schools, teachers and students. The iPad as an open educational tool encourages a student-centered model of learning, whereas teachers predominantly use frontal teaching methods. Furthermore, the teachers in the two countries have considerably different perceptions and expectations regarding the role and outcome of mobile technology.